2016
DOI: 10.2134/jeq2015.06.0303
|View full text |Cite
|
Sign up to set email alerts
|

Path Analyses of Grain P, Zn, Cu, Fe, and Ni in a Biosolids‐Amended Dryland Wheat Agroecosystem

Abstract: Land application of biosolids is an effective means of recycling plant nutrients and is the primary method of biosolids reuse endorsed by the USEPA. One issue concerning biosolids application is the extent of the contribution of biosolids-borne plant nutrients to the overall crop concentration and uptake or removal of these nutrients. We studied the effects of biosolids application on wheat ( L.) grain P, Zn, Cu, Fe, and Ni concentrations and uptake (removal) at two dryland agroecosystem sites from 1993 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…(2020) also reported that biosolids application increased bahiagrass tissue Mg and Zn concentrations by 12% and 21% compared to inorganic fertilizer, respectively. The increase in tissue Zn concentrations in response to biosolids application was also reported in long‐term (11‐ to 20‐year long) field experiments with wheat ( Triticum aestivum L.) (Barbarick et al., 1995, 2016). Increased tissue Cu concentration in response to biosolids application has been reported in a field study with bahiagrass (Adjei & Rechcigl, 2002) and in long‐term studies with wheat (Barbarick et al., 1995, 2016).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…(2020) also reported that biosolids application increased bahiagrass tissue Mg and Zn concentrations by 12% and 21% compared to inorganic fertilizer, respectively. The increase in tissue Zn concentrations in response to biosolids application was also reported in long‐term (11‐ to 20‐year long) field experiments with wheat ( Triticum aestivum L.) (Barbarick et al., 1995, 2016). Increased tissue Cu concentration in response to biosolids application has been reported in a field study with bahiagrass (Adjei & Rechcigl, 2002) and in long‐term studies with wheat (Barbarick et al., 1995, 2016).…”
Section: Discussionsupporting
confidence: 58%
“…The increase in tissue Zn concentrations in response to biosolids application was also reported in long-term (11-to 20-year long) field experiments with wheat (Triticum aestivum L.) (Barbarick et al, 1995(Barbarick et al, , 2016. Increased tissue Cu concentration in response to biosolids application has been reported in a field study with bahiagrass (Adjei & Rechcigl, 2002) and in long-term studies with wheat (Barbarick et al, 1995(Barbarick et al, , 2016. In contrast to our data, previous studies demonstrated no difference between inorganic fertilizer and biosolids application on bahiagrass tissue Mg (Adjei & Rechcigl, 2002;Tiffany et al, 2001a).…”
Section: Bahiagrass Tissue Mineral Concentrationsupporting
confidence: 65%
See 2 more Smart Citations
“…• The extent of biosolids-borne plant nutrients to overall crop nutrient concentration, uptake, and ultimately off-site removal. Barbarick et al (2016) used pathway analysis, in combination with multiple linear regression, to identify the (in)direct and total effects of repeated biosolids applications (over a 20-yr period), soil extractable elements, soil pH, and organic C content on removal of P, Zn, Cu, Fe, and Ni in wheat grain. The authors noted that (a) the number of biosolids applications had the greatest positive effect on grain nutrient removal, and (b) AB-DTPA-extractable Cu content was positively correlated with plant Cu uptake.…”
Section: North Bennett Co Biosolids Land Application Research Programmentioning
confidence: 99%